Human papillomavirus genotype prevalence and distribution among Moroccan women - Birrou, Kamal; Tagajdid, Mohamed Rida; annaz, Hicham El; Elkochri, Safae; Abi, Rachid; Zouhdi, Mimoune; Mrani, Saad (International Journal of Research in Medical Sciences, 2017)
Background:Human papillomavirus (HPV) is the major etiologic agent of invasive cervical cancer, vulvar and vaginal cancer. It has been estimated that, worldwide, 70% of cervical cancers are due to HPV-16 and HPV-18. Malignant transformation appears to require the presence of additional cofactors such as pregnancy, smoking and immunosuppression. The aim of the present study was to determine the prevalence and distribution of HPV genotypes among Moroccan women. Methods:Between January 1, 2011, and December 31, 2012, 277 cervical samples collected from confirmed women who attended the department of gynecology and obstetrics at Mohamed V Military teaching hospital, Rabat, Morocco, were analyzed in the laboratory of virology for HPV in vitro diagnosis and genotyping and for cytology in laboratory of pathology. Results:High-risk HPV DNA was detected in 101 (36%) samples, with higher prevalence in women ≥45 (43%) years. The overall prevalence of HPV infection and multiple infections in the study samples was 76% and 21%, respectively. The most frequent HPV genotypes were HPV-16 (31%). Human papillomavirus DNA detection was inversely related to maternal age. The risk of HPV infection was significantly reduced in women aged older than 30 years. The history of gynaecological problem showed significant association with the HPV positive test. Conclusion:In Morocco, the diagnosis of cervical lesions rests exclusively on the cytology-based screening that offers substantial protection, although current coverage is low. The introduction of HPV DNA testing in cervical cancer management will greatly benefit early stage HPV detection and help prevent development of cervical lesions and cancer. Screening pregnant women offer a significant opportunity for the Moroccan National Program against cervical cancer to control.